Enhanced Active Filter for Single-Phase Controlled Rectifier Applications - Jacob Dethan; Abidin Abidin; Benny Daniawan; Rino Rino (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
Active filter can be used to increase the performance of single-phase controlled rectifier by reducing the generated ripple and harmonic distortion. Active filter can also increase power factor and efficiency of thyristor. In this work, active filter was designed by using NPN Bipolar Junction Transistor (BJT) compared with active filter created by utilizing NPN Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The obtained efficiency of BJT based active filter with firing angles of 0° to 90° were 87.01% - 96.67%. Whereas, MOSFET based active filter produced comparable efficiency between 90.62% - 96.07%. It can be seen that MOSFET based active filter produced higher efficiency at firing angle of 0° which was 90.62% compared to BJT based active filter that has produced efficiency of 87.01% at the same firing angle. Both active filters obtained similar power factors within the range of 0.57 lagging – 0.92 lagging. It is expected that this work can be useful for the design of active filters for various power electronics applications including the design of High Voltage Direct Current (HVDC) power transmission system.